System-based probabilistic evaluation of longitudinal seismic control for a cable-stayed bridge with three super-tall towers. (15th February 2021) - Wei, Biao; Hu, Zhangliang; He, Xuhui; Jiang, Lizhong
Highlights: Cable-stayed bridge with three super-tall towers. The partial constraint system is the optimal structural system of such bridge. Evaluation of the effect of fluid viscous damper and cable restrainer is conducted. Fluid viscous dampers have better effect than cable restrainers for such bridges. Abstract: The system fragility method was used to evaluate the seismic structural systems and seismic mitigation devices for a cable-stayed bridge with three super-tall towers. Firstly, a three-dimensional numerical model of a four-span cable-stayed bridge with middle-tower height of 332 m was simulated using OpenSEES, which accounted for the material and geometric nonlinearities; 80 actual ground motions were chosen for conducting time history analysis. Secondly, the fragility curves of the components and the system were derived using general fragility theory and Product of the Conditional Marginal theory, respectively. Then, three longitudinal seismic structural systems were evaluated. Finally, under the optimal seismic structural system, the optimal parameters of the longitudinal fluid viscous damper and cable restrainer were obtained using the response surface method, and the mitigation effects of the fluid viscous damper and the cable restrainer with optimal parameters were compared using fragility curves. The results show that different structural systems and mitigation devices have significant influence on the damage control of displacement and stay cable force. The super-tall tower cable-stayed bridge with a partial constraint system of the consolidated middle tower and floating side towers has the lowest damage probability; and the longitudinal fluid viscous damper and cable restrainer can achieve a certain mitigation effect, however, the fluid viscous damper has better effect. Therefore, the partial constraint system and fluid viscous damper should be used in the longitudinal direction of the multiple super-tall-tower cable-stayed bridge.